Use of real patients in teaching ENT diseases to undergraduate students and its effects on patient satisfaction: cross-sectional survey. Issue 7 (July 2015) - Löfgren, E; Alikoski, S; Hannula, S; Sorri, M; Alho, O-P
Abstract Objectives: To describe a method of using real patients in teaching ENT to undergraduates and to examine whether being a case patient affected patient satisfaction. Methods: In a cross-sectional study, 68 teaching-involved patients (case patients) with a suspected common ENT illness and 68 matched (in terms of age, sex and region of complaint) control patients evaluated the health service and their encounter with the physician. The students saw the case patients first independently and then saw the patient with the teacher physician. The controls were treated in a normal way. Results: Fifty-eight case patients (84 per cent) and 65 control patients (95 per cent) answered the questionnaire. The median duration of the visit was significantly longer for the case patients than the controls (115 vs 60 minutes). Almost all patients in both groups graded the overall quality of the health service, and the variables describing various aspects of the setting and the encounter with the physician, as either good or excellent. Conclusion: Patients who took part in the undergraduate teaching of ENT diseases were equally content with their primary visit as the control patients, even though their visit took a markedly longer time.